Structure Dyadic Method in Improving the Students’ Ability in Reading Comprehension - Bunyamin Bunyamin; Fatma Sari; Mawaddah Rahanyamtel (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The purpose of this study was to analyze the improvement of reading learning outcomes for students of the English Study Program of Tarbiyah Faculty of State Islamic College Sorong, using the Structure Dyadic Method (SDM). This method is a method that only consists of two members in one group (dyad) and its technical implementation is very structured. This research used quantitative methods. There was one problem that was analyzed using statistical analysis, namely the effect of the SDM on the reading ability of the English study program students of Tarbiyah Faculty of State Islamic College of Sorong. Researchers took data using pretest and posttest. The results showed that the use of the SDM in reading comprehension was very good in improving the students' ability to read descriptive texts.